Oxydative stress, endothelial dysfunction and atheroesclerosis - Lara Terán, Joffre (2014)
Many of the cardiovascular diseases pathologic components are closely related to reactive oxygen species (ROS) metabolism deregulation (oxidative stress). For example, LDL oxidation, endothelial dysfunction and inflammatory processes are partially mediated by increase of cellular ROS production. Other conditions associated with cardiovascular disease as insulin resistance and metabolic syndrome are also characterized by ROS overproduction and excessive oxidative stress. In this article ROS participation in these pathologic processes is reviewed.